Exploring Humor Functions in Trevor Noah Stand Up Comedy: I Wish You Would - Sausina, Cut Nina (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2023)
This study discusses the function of humor in Trevor Noah's Stand-Up Comedy entitled I Wish You Would. The aims of this study are to examine the humor functions applied by Trevor Noah in his stand-up comedy and to contribute in filling the existing gaps . The first question to answer to what extent Trevor Noah’s SUC fit Hay (2000) humor’s function theory. The second question to answer how the utterances of Trevor Noah’s jokes fit the humor functions. The data in this research are oral data which is transcribed into written form. This study uses a qualitative descriptive method. According to the study in the stand-up comedy entitled I wish I would, the writer found that Trevor Noah uses almost all aspects of humor function .